The migratory flows in Spain: an analysis of the migration and immigration input from European Union - VALERO-MATAS, Jesús; COCA, Juan; MIRANDA-CASTAÑEDA, Sergio (Papeles de Población; Vol. 16 Núm. 65 (2010), 2010)
External migration has always been present in Spanish history. Few years ago Spanish people has migrated to Latin-Americans and Europe countries. Now, as Spain has ceased to be a sender of immigrants and has become a receiver of such, it may seem that emigration no longer exists at all. Reality tells us differently. Also Spain, especially since 1986 (when it joined the European Union) has meant a large-scale transformation went from being a country of emigrants to a country of immigrants. In this article we show this process and the social consequences of this one.